Charging Station for Two-wheelers Electric Vehicle Powered by Photovoltaic System - Iskandar, Handoko Rusiana; Haz, Fauzia (Program Studi Teknik Elektro Universitas Khairun, 2025)
Indonesia has significant solar energy potential, ranging from 4.88-5.78 kWh/m2 /day with a production of 444 GWh by 2022, which is supported by various government initiatives and research projects focused on renewable energy-based two-wheeled electric vehicles. The increasing prevalence of electric vehicles in Indonesia necessitates the adaptation of photovoltaic (PV)-based renewable energy infrastructure to provide power sources for battery-operated two-wheeled electric vehicle charging stations. This paper presents proposals for the implementation of two-wheeled electric vehicles, utilizing various battery technologies combined with PV-based renewable energy systems, incorporated into various plans and schemes. The research methodology was developed by evaluating the electric vehicle battery requirements and system component capacities, while the charging cycle describes the relationship between the battery capacity and the capacity of 200 Wp, 400 Wp, and 500 Wp photovoltaic panels. The calculation results show that the charging system uses various PV panel capacities. The 200 Wp PV panel requires the longest charging duration. The 400 Wp photovoltaic panel serves as an intermediate charging station. The 500 Wp photovoltaic panel shows the fastest charging duration among the three types of panels, ranging from 1 to 3.7 hours, depending on the battery load rating of the electric wheeled vehicle. In addition, the proposed PV charging system provides various battery capacity options with consideration of autonomous time (1-4 days) where the charging time of 4 days for electric vehicle battery capacity 2000 Wh will be in line with the battery demand in the charging station.